Strategies, Best Practices, and Challenges in Quality Management in Senior High Schools - Aini Mahfudhoh Aini; Agus Zaenul Fitri; As’aril Muhajir (JIEMAN: Journal of Islamic Educational Management, 2026)
This study employs a Systematic Literature Review (SLR) to examine quality management strategies, best practices, and implementation challenges in Indonesian senior high schools (SMA). Although previous studies have investigated various dimensions of quality management, including Total Quality Management (TQM), School-Based Management (SBM), and quality assurance systems, existing evidence remains fragmented and lacks a comprehensive synthesis at the national level. Literature was retrieved from Scopus, Web of Science (WoS), Dimensions, and SINTA databases. Following the PRISMA framework, 24 peer-reviewed articles published between 2015 and 2025 were selected for analysis. The findings indicate that TQM, SBM, the PDCA cycle, quality assurance mechanisms, and transformational leadership are the most prominent quality management strategies. Effective practices integrate strategic planning, stakeholder engagement, curriculum development, and continuous improvement processes. However, implementation remains constrained by limited resources, human resource capacity, resistance to change, and policy-related challenges. This study contributes to the theoretical understanding of educational quality management by synthesizing the relationships among quality management strategies, best practices, and implementation challenges in Indonesian senior high schools. In practice, the findings provide evidence-based insights for school leaders and policymakers in developing adaptive, sustainable quality improvement initiatives.